African and Asian Economies: Comparative Analysis on Public Procurement and Public Financial Management - Amankwa, A. (H. : ĐHKT, 2020)
Public Procurement process inadvertently affects the economic growth of countries. In developing countries, procurement processes have been politicized, bastardized and not transparent. The skyrocketing discrepancies in Africa has become overly worrisome and breeds corruption. Despite efforts of governments to sanitize public procurement in Africa and improve Public financial management, there seem to be no sustainable solutions promulgated to end it. However, in contributing to the extant literature on public procurement, this paper makes a case for Nudging as the theoretical framework underpinning the study. Furthermore, a comparative analysis between Asia and Africa shows an inverse trend of sustainable procurement; the former advancing in sustainable procurement processes and the latter in a state retrogression. With a descriptive case study design of data from peer reviewed journals, the paper examines the nosedive of public procurement process in Africa as compared with Asia. Japan, Singapore, Nigeria and Ghana were chosen for the comparative analysis. Data from (2010 – 2017) was gathered from Global Integrity Index (GII) of Transparency International, World Bank’s Country Policy and Institutional Assessment (CPIA) and Global Economy. From the nudging theory, the paper discovers palpable advancement of procurement processes in Asia juxtaposed with Africa: These are uncompromising regulations, altering culture, citizen charters and sanctioning defaulters. The study realized that, the culture and values of blacklisting and sanctioning unlawful behaviors of suppliers is fully sanctioned in most countries in Asia. However, corruption and politicization drive procurement processes in developing countries. Moreover, Africa is characterized with high debts and public funds for debt reliefs and reforms do not commensurate with the procurement sequel of reforms in Africa.